Nymphal development of Rhopalus maculatus and Chorosoma schillingii (Hemiptera: Heteroptera: Rhopalidae: Rhopalinae) and development of trichobothrial pattern in Rhopalidae - Rohanová, Markéta; McPHERSON, J E; Vilímová, Jitka (Zootaxa, 2019)
The nymphal morphology of the family Rhopalidae is well known for several species, most of which are pests. Ontogenetic changes in morphology are described in detail for two members from two tribes of the subfamily Rhopalinae, Rhopalini: Rhopalus (Aeschyntelus) maculatus (Fieber) and Chorosomini: Chorosoma schillingii (Schilling). Keys to the nymphal instars of both species are provided. The special types of nymphal setae and lateral abdominal processes are described in R. maculatus. The ontogenetic development of abdominal trichobothria is described, and the known trichobothrial patterns within the Rhopalidae are discussed.
Keywords: Heteroptera; sensilla; Nymph; nymfa; Animals; Hemiptera; velikost těla; zvířata; velikost orgánu; Body Size; Sensilla; Organ Size